2017
DOI: 10.1038/srep44606
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of SOD1 mutations in a Chinese population with amyotrophic lateral sclerosis: a case-control study and literature review

Abstract: Although the copper/zinc superoxide dismutase-1 (SOD1) gene has been identified in both familial ALS (FALS) and sporadic ALS (SALS), it has rarely been studied in Chinese patients with ALS, and there are few studies with large samples. This study sought to assess the prevalence of SOD1 mutations in Chinese ALS patients. We screened a cohort of 499 ALS patients (487 SALS and 12 FALS) from the Department of Neurology at the West China Hospital of Sichuan University and analyzed all coding exons of SOD1 by Sanger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 54 publications
1
20
1
Order By: Relevance
“…The mean AAO of the SOD1 -mutant patients in this study was 43.92 (95% Cl 41.61–46.23) years, which was younger than that of 45.5 years reported in a southwest China [35] study that identified only 8 patients carrying mutant SOD1 genes among 499 ALS patients. This mean AAO is also younger than that of the overall Chinese ALS population (49.7, 95% Cl 49.2–50.3) [38] and younger than that of SOD1 -mutant patients reported in Canada (48.9) [49] and the United States (46.9–49.7) [29, 50].…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…The mean AAO of the SOD1 -mutant patients in this study was 43.92 (95% Cl 41.61–46.23) years, which was younger than that of 45.5 years reported in a southwest China [35] study that identified only 8 patients carrying mutant SOD1 genes among 499 ALS patients. This mean AAO is also younger than that of the overall Chinese ALS population (49.7, 95% Cl 49.2–50.3) [38] and younger than that of SOD1 -mutant patients reported in Canada (48.9) [49] and the United States (46.9–49.7) [29, 50].…”
Section: Discussioncontrasting
confidence: 75%
“…Of note is the gender difference in patients harbouring SOD1 mutations. Male predominance was present but mild in SOD1 -mutant patients (M: F of 1.2 overall, 1.3 in fALS, and 0.9 in sALS); these ratios are lower than those in other reports from China (5/3 = 1.6) [35], Taiwan (7/5 = 1.4) [36], and Iran (4/3 = 1.3) [37] despite the small sample sizes in those studies. These ratios are also lower than those in both the present cohort (689/393 = 1.75) and in the ALS population in China (1.47–1.7) [35, 38]; however, they are comparable to that of SOD1 -mutant patients found in the United States (1.3, 175 fALS included) [29].…”
Section: Discussionmentioning
confidence: 62%
“…As predicted by ConSurf ( S2 Fig), the amino-acid substitution A4V and H46R occur at known conserved regions of SOD1 [21,35,87]. Although our results indicated that the variant I113T occurs in a variable position, this amino-acid is evolutionarily conserved in mammals [88]. The variant D90A, in turn, was predicted to affect an average conserved position.…”
Section: Plos Onesupporting
confidence: 52%
“…We and display a defect in neuronal survival compared to neurons derived from control fibroblasts 31,53,54 . However, iPSC lines derived from patient fibroblasts with less common SOD1 mutations associated with ALS, I113T [55][56][57] and H44R 58 , have not been previously 86.1% (0.68 AUC), with a markedly higher accuracy for live neurons (91.2%) than dead ones (41.4%) ( Figure 6D). Across balanced randomized batches of data, GEDI-CNN averaged only 70% accuracy, and was not significantly different from human curation accuracy, indicating that death is difficult to discern from the EGFP morphology alone in this dataset ( Figure 6E).…”
Section: Zero-shot Transfer Application Of Gedi-cnn To Human Ipsc-dermentioning
confidence: 99%